Rola poznańskiej Wyższej Szkoły Ekonomicznej w rozwoju polskiej nauki i praktyki gospodarczej - Pokorzyński, Lucjan (Wydział Prawa i Administracji UAM, 1967)
On the occasion of the fortieth anniversary of the Poznań School of Economics (1926—1966) the author takes a synthetic view of all scientific researches made there mainly between 1957 and 1966. The survey is to characterize the part played by the Poznań College in scientific and economic life. The author begins his short view with the outline of the organizational structure of the College in its present state and then goes over to contemplating the forms and possibilities of the influence which a high school of economics can exert upon the framing of economic thought and the practice of economic life. After having stated that the position of a school of university status as well as its character and intensity of its influence are, to a large extent, conditioned by trie level, scope and results of scientific research made, the author presents a synthetic survey of the basic problems worked out in the College during the last ten years i.e. in a period when scientific thought had no longer encountered any obstacles and restrictions connected with the past stage of scientific schematism and conformity. The author groups the problems according to their belonging to different fields and disciplines and in particular to political economy of capitalism and socialism, planning and economic policy, branch economics (industry, home trade, international trade, agriculture, transport), sociology, statistics, finance and insurance, economic geography, economic history, law, accounting, cooperation, product determination and chemistry. The author points out that the College concentrates its interest on the most up to date problems, both theoretical and connected with the practice of economic life during the period of reconstruction of the system of management and control of national economy. The author also emphasizes the frequent participation of scientific workers of the College in the economic life of the country, as well as their active part taken in the exchange of scientific thought between scientists from Poland and abroad, by attending different scientific meetings and conferences and by their personal, individual scientific contacts.
Poznań school of economics and its part in the development of polish science and economic practice